Unusual Occurrence of Peripheral Ossifying Fibroma in an Elderly Male - Gaekwad, Shivali Surendra Rao; Hegde, Usha; Gujjari, Sheela; Kumar, SC Veerendra; Vidyapriyadharshini, DS (Journal of Orofacial Research, 2013)
The present case is a scenario of occurrence of relatively common peripheral ossifying fibroma in an uncommon site of occurrence. It was noted in the maxillary posterior region incontrast to its usual occurrence in anterior maxillary region. The lesion was observed in elderly male subject aged 64 years, contradictory to its usual predilection for young females in thesecond or third decade of life. As this case contradicts the common norms of predilection of the lesion with regard to age, gender and site, it emphasizes the need for looking beyond theconventional norms for proper diagnosis and prompt treatment.